Matos, Violante Saramago (2022). De memórias nos fazemos. Lisboa: Edições Esgotadas. 132 pp. ISBN: 978-989-9092-25-9 - Pinheiro, Joaquim (CEM – Cultura, Espaço & Memória, 2023)
DOI: https://doi.org/10.21747/2182-1097/cem15r2